2021
DOI: 10.1002/glia.23984
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging the replication‐competent avian‐like sarcoma virus/tumor virus receptor‐A system for modeling human gliomas

Abstract: Gliomas are the most common primary intrinsic brain tumors occurring in adults. Of all malignant gliomas, glioblastoma (GBM) is considered the deadliest tumor type due to diffuse brain invasion, immune evasion, cellular, and molecular heterogeneity, and resistance to treatments resulting in high rates of recurrence. An extensive understanding of the genomic and microenvironmental landscape of gliomas gathered over the past decade has renewed interest in pursuing novel therapeutics, including immune checkpoint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 127 publications
(269 reference statements)
0
15
0
Order By: Relevance
“…We leveraged the RCAS/ tv‐a modeling system (Kanvinde et al, 2021), used previously by our group to study gliomagenesis in immunocompetent rats (Connolly et al, 2017; Connolly et al, 2018), to generate a model for Fn14‐high human gliomas. One cohort of tv‐a transgenic rat pups received an intracranial injection of equal amounts of DF‐1 cells transfected with RCAS‐PDGF‐A and RCAS‐shp53 constructs to serve as the Fn14‐low group ( n = 31) while another cohort received the same two constructs in equal combination with an RCAS‐Fn14 construct to serve as the Fn14‐high group ( n = 19) (Figure 1(c)).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We leveraged the RCAS/ tv‐a modeling system (Kanvinde et al, 2021), used previously by our group to study gliomagenesis in immunocompetent rats (Connolly et al, 2017; Connolly et al, 2018), to generate a model for Fn14‐high human gliomas. One cohort of tv‐a transgenic rat pups received an intracranial injection of equal amounts of DF‐1 cells transfected with RCAS‐PDGF‐A and RCAS‐shp53 constructs to serve as the Fn14‐low group ( n = 31) while another cohort received the same two constructs in equal combination with an RCAS‐Fn14 construct to serve as the Fn14‐high group ( n = 19) (Figure 1(c)).…”
Section: Resultsmentioning
confidence: 99%
“…The RCAS/ tv‐a system has proven to be a valuable tool to recapitulate key elements of human gliomas in an immunologically intact host microenvironment (Kanvinde et al, 2021). In our prior reports using this system, we showed that (i) elevated Fn14 expression in mouse astrocytes increased their proliferative and migratory capacity (Fortin et al, 2012), and (ii) combined PDGF‐A overexpression and p53 depletion in rat neural precursor cells reproducibly generated brain tumors with many of the key features characteristic of mouse and human proneural‐like gliomas (Connolly et al, 2017; Connolly et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One retrovirus-based system that displays these characteristics is the replication-competent avian sarcoma-leukosis virus (RCAS)/tumor virus receptor-A (tva) system [ 41 ]. As illustrated in Figure 1 A, the RCAS virus offers a multicloning site for the insertion of genetic information with a maximum of 2.5 kilobase (kb), which is controlled by the viral LTR promoter [ 42 ]. Viral replication solely takes place in cells expressing the tva receptor, which is essential for viral entrance.…”
Section: Introductionmentioning
confidence: 99%